'Héloïse': towards a co‐ordinated ecosystem approach for the archiving of scientific publications?. Issue 3 (1st July 2013) - DILLAERTS, Hans; CHARTRON, Ghislaine
ABSTRACT: With the continued development of open access policies, it is important to promote consensus‐building projects with the various stakeholders. This article gives an account of how such collaboration has facilitated the construction of the project Héloïse. This project is a French information service dedicated to describing the policies of French publishers on the self‐archiving of scientific publications. Héloïse represents a real tool of mediation whose development involved much debate between publishers and research stakeholders. This article seeks to demonstrate that the development of trust between the actors involved in the project was a major component of its success.